P623 Mucosal eosinophils as markers of post-induction vedolizumab response in paediatric Ulcerative Colitis. (30th January 2023) - Musto, F; Ranalli, M; Giordano, C; Bianchi, E; Veraldi, S; Oliva, S; D'Arcangelo, G; Aloi, M
Abstract: Background: Vedolizumab (VDZ) is commonly used as an off-label therapy in children with ulcerative colitis (UC) but no predictive factors of response are available. Vedolizumab binds α4β7 integrin and blocks the migration of T-lymphocytes and other cells, including eosinophils, which are involved in the UC inflammatory process. The aim of our study was to explore the predictive value of pre-therapy mucosal eosinophil count on the response to vedolizumab induction therapy in a paediatric population with UC Methods: This is a retrospective, monocentric study, including children with UC treated with VDZ in the Paediatric Gastroenterology Unit of Policlinico Umberto I Hospital – Sapienza University of Rome. Histopathological data were analyzed for eosinophil counts in high power fields (hpf) in the cecum, transverse colon, sigma, and rectum prior to VDZ treatment. Clinical remission and response were evaluated at week 14 based on the PUCAI score. Results: Twenty-five UC patients treated with VDZ were enrolled. All patients had failed previous anti-TNF therapy. Median baseline eosinophil count was 21 eo/hpf (5-60) in the cecum, 20 eo/hpf (6-68) in transverse colon, 44 eo/hpf (12-77) in sigma and 31 eo/hpf (9-67) in rectum. Baseline median eosinophil mucosal count in sigma was significantly higher in patients in remission (51[30-82]/ vs. 19[8.5–46] eosinophils/hpf, P <0.05) and clinical response (46[23-79]/ vs. 14[6–45] eosinophils/hpf, P <0.05) at week 14, compared to non-responders. At univariate and multivariate analysis, the number of eosinophils in sigma was confirmed to predict clinical remission [OR=1.0 (95%CI:1.00-1.087), p: 0.03), also independently to concomitant steroid use [OR: 1.06 (95%CI: 1.00-1.122) p: 0.047). The ROC curve identified a risk threshold value for eosinophil count in sigma >23 eosinophils/hpf, with a sensitivity of 85.7% and specificity of 66.7% (Youden's index 0.83) with an area under the curve (AUC) of 0.778 Conclusion: Mucosal eosinophil abundance in sigma may predict remission to vedolizumab induction in paediatric UC. More studies are warranted to confirm these preliminary results and further investigate the role of mucosal eosinophils as a marker of therapeutic response and in the pathogenesis of UC